METODE BELAJAR ADAB DALAM UPAYA MENGISI KEGIATAN BELAJAR DI BULAN RAMADHAN PADA SISWA SISWI MUSHOLLA NURUL JANNAH KEC. KARAWACI TANGERANG - Siti Maesaroh (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2023)
Religious guidance for youth is necessary and must be carried out as much as possible. This development can be carried out through education. Whether it's religious education, education in schools, or education in society. In studying religion, it is necessary to know the adab method in learning activities. Adab is a very important part of education, related to aspects of attitudes and values, both individually and socially related. The service method used in this service is socialization and qualitative descriptive method, the intention is to socialize a method that expresses certain social situations by describing reality correctly, formed by words based on data collection techniques and relevant data analysis obtained from natural situations. This service was held at the Musholla Nurul Jannah, Jl. Proklamasi RT: 001/ 009 Kel. Cimone, Kec. Karawaci, Kota Tangerang 15114. The subjects of the service were chosen based on the specific objectives of the authors which include: leaders, teachers, parents, and students of the Musholla Nurul Jannah. The community service program can be carried out properly and run smoothly by the method of implementing the activities that have been prepared, although not all of the young people of Musholla Nurul Jannah have mastered the material presented well. This activity received a very good reception as evidenced by the presence of the young children of Musholla Nurul Jannah in participating in the joint education by not leaving the place before the activity time ended.